2019
DOI: 10.1519/jsc.0000000000003431
|View full text |Cite
|
Sign up to set email alerts
|

Acute Capsaicin Supplementation Improved Resistance Exercise Performance Performed After a High-Intensity Intermittent Running in Resistance-Trained Men

Abstract: Acute capsaicin supplementation improved resistance exercise performance performed after a high-intensity intermittent running in resistance-trained men. J Strength Cond Res 36(1): 130-134, 2022-We sought to investigate the acute effects of capsaicin supplementation on the rate of perceived exertion (RPE) and heart rate during high-intensity intermittent exercise (HIIE) and resistance exercise performance executed after HIIE in resistance-trained men. Eleven resistance-trained men completed 2 randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 34 publications
(60 reference statements)
4
23
1
Order By: Relevance
“…Such improvement was verified through the increase in the number of maximum repetitions performed and, consequently, in the total volume performed by the individuals of the experimental group. Similar results were found by Freitas et al 16 , in which acute capsaicin supplementation improved the performance in resistance training, after performing a previous protocol of high-intensity interval training (HIIT). The result of this study demonstrated that capsaicin supplementation resulted in lower RPE in HIIT and improved performance in subsequent resistance training.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Such improvement was verified through the increase in the number of maximum repetitions performed and, consequently, in the total volume performed by the individuals of the experimental group. Similar results were found by Freitas et al 16 , in which acute capsaicin supplementation improved the performance in resistance training, after performing a previous protocol of high-intensity interval training (HIIT). The result of this study demonstrated that capsaicin supplementation resulted in lower RPE in HIIT and improved performance in subsequent resistance training.…”
Section: Introductionsupporting
confidence: 86%
“…Each participant consumed two identical capsules before performing the exercise: capsaicin (12 mg) and placebo (starch); or caffeine (400 mg ≅ 5 mg.kg −1 ) and placebo; capsaicin and caffeine (12 mg + 400 mg ≅ 5 mg. kg −1 ; respectively), or placebo and placebo (Centralfarma, Ipatinga, Brazil). The 12 mg dose of capsaicin was adopted based on the results of the studies by Freitas et al 13 and Freitas et al 16 , who found positive effects on resistance training performance from acute supplementation of this substance (≅ 5 mg.kg −1 ). The relative caffeine dosage was adopted based on the literature, which indicates that such approximate values can be effective for increasing physical performance and safe for the volunteers 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies from our research group have used 12 mg of CAP 45 min before the exercise investigating different type of protocols (400, 1500, and 3000 m and in high-intensity intermittent exercise) in physically active men [ 12 , 13 , 14 ]. Additionally, improvements in combined exercise protocols, such as 5 km running plus strength exercise were detected applying 24 mg of CAP in two doses of 12 mg with 45 min interval between doses [ 15 ]. On the other hand, another study showed improved endurance performance using 150 mg CAP administered 60 min before a 30 min aerobic cycle ergometer exercise bout, demonstrating higher fat oxidation under CAP conditions compared to PLA [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our research group found an improvement in performance applying 12 mg of CAP 45 minutes before different types of exercise and protocols (400 meters; 1.500 meters; 3.000 meters and high-intensity intermittent exercise) in physically active men [12][13][14]. Additionally, improvements in combined exercise protocols, such as 5-km running plus strength exercise were detected applying 24 mg of CAP in two doses of 12 mg with 45 minutes interval between doses [15]. On the other hand, another study showed improved endurance performance using 150 mg CAP administered 60 minutes before a 30 min aerobic cycle ergometer exercise bout, demonstrating higher fat oxidation under CAP conditions compared to placebo [16].…”
mentioning
confidence: 99%